2021
DOI: 10.1002/cssc.202100757
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Active Sites for CO2 Reduction on Graphene‐Supported Single‐Atom Catalysts

Abstract: Transition metal-and nitrogen-codoped graphene (referred to as MÀ NÀ G, where M is a transition metal) has emerged as an important type of single-atom catalysts with high selectivities and activities for electrochemical CO 2 reduction (CO 2 R) to CO. However, despite extensive previous studies on the catalytic origin, the active site in MÀ NÀ G catalysts remains puzzling. In this study, density functional theory calculations and computational hydrogen electrode model is used to investigate CO 2 R reaction ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Kang et al combined DFT calculations and experimental investigation to study the catalytic ability of Zn-NG catalyst with Zn-N 3 sites for CO 2 RR. [163] Because *OCHO adsorbent was produced in the process of pronation, the single-atom Zn coordinated with N and C in the Zn-NG catalyst cannot be used as the active site for CO generation, which was inconsistent with many studies. They found that the real active sites were C atoms bonded by Zn atoms, which had high activity.…”
Section: Adjusting the Number Of Ligandsmentioning
confidence: 99%
“…Kang et al combined DFT calculations and experimental investigation to study the catalytic ability of Zn-NG catalyst with Zn-N 3 sites for CO 2 RR. [163] Because *OCHO adsorbent was produced in the process of pronation, the single-atom Zn coordinated with N and C in the Zn-NG catalyst cannot be used as the active site for CO generation, which was inconsistent with many studies. They found that the real active sites were C atoms bonded by Zn atoms, which had high activity.…”
Section: Adjusting the Number Of Ligandsmentioning
confidence: 99%
“…The N 1s spectrum was deconvoluted into three major peaks indicating pyridinic, Ni−N, and pyrrolic N contents. The pyridinic and pyrrolic nitrogen served as the coordinating sites for Ni 2+ , [43,44] and the binding energy at 399.4 eV was ascribed to the coordination of Ni to nitrogen (Figure 3a). [45] The Ni 2 p spectrum indicated two dominant peaks at 854.3 and 871.9 eV for Ni 2 p 3/2 and Ni 2 p 1/2 , respectively (Figure 3b), which were attributed to the Ni 2+ state of nitrogen‐coordinated Ni, [46] whereas Ni 2 p spectrum for Ni/C catalyst were deconvoluted in Ni 0 , and Ni 2+ states (Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…[25] In the past few years, single-atom catalysts (SACs) have attracted extensive attention in the field of catalysis due to their near-unity atom efficiency thus minimizing the use of precious metals. [26][27][28] In particular, single-atom modified MOFs have been studied as catalysts for CO 2 reduction reactions. [15,29,30] Notably, photoactive organic or metal-organic complexes are used as ligands to construct single-atom MOFs, which can produce photocatalytically active MOFs with isolated catalytic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of reusable heterogeneous photocatalysts for CO 2 reduction is imminent [25] . In the past few years, single‐atom catalysts (SACs) have attracted extensive attention in the field of catalysis due to their near‐unity atom efficiency thus minimizing the use of precious metals [26–28] . In particular, single‐atom modified MOFs have been studied as catalysts for CO 2 reduction reactions [15,29, 30] .…”
Section: Introductionmentioning
confidence: 99%